Stock Price and Profitability: an Impact Analysis in the Consumer Products Industry in Indonesia - Agustina, Heni; Lestari, Fitria; Putra, Riyan Sisiawan (GREENOMIKA, 2024)
This study aims to determine the effect of profitability (ROA, ROE, ROS, and NPM) on stock prices. The population in this study are consumer goods industry sector companies listed on the Indonesia Stock Exchange. The retrieval method uses the Purposive Sampling method. Samples were collected from 8 consumer goods industry sector companies listed on the Indonesia Stock Exchange during the period 2019 - 2022. The research used is associative research with a quantitative approach. Data analysis techniques use descriptive statistics, classic assumption tests. While hypothesis testing uses multiple linear regression analysis. The results of this study indicate that partially profitability (ROA, ROE, ROS, and NPM) has a positive and significant effect on the company value of consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2019-2020.